Status Quo of City Logistics in Scientific Literature: Systematic Review - Wolpert, Stefan; Reuter, Carsten (Transportation Research Record, 2012)
Roadway infrastructure is reaching maximum capacity in urban areas because of expanding urbanization, demographic changes, and continuously increasing freight volumes. An overview of the latest research on city logistics is needed to address these challenges, and a review of the scientific literature is presented. A specifically designed framework for systematic literature review was used to analyze 92 relevant articles from prominent electronic databases. A taxonomy of city logistics literature was created to aid academics and practitioners and to stimulate interest of other parties in this area.<br